Sociological Analysis of Law on Witness Susi, Household Assistant Ferdi Sambo in the Case of Premeditated Murder in the Testimony of the Defendant Eliezer - Vicki Dwi Purnomo; Nur Zanis (PT FORMOSA CENDEKIA GLOBAL, 2022)
In writing this paper, writing took as an example the case of Witness Susi, Household Assistant Ferdy Sambo, the author conducted research in this paper as follows: how are the sociological laws in dropping Susi's testimonies, which are overlapping and convoluted. This case study aims to find out the agenda setting in the death case of Brigadier Novriansyah Yosua Hutabarat Brigadier J by his superior, Inspector General Ferdy Sambo. Based on the results of the research, a person may be subject to criminal perjury or perjury if the following elements are met: There is a legal subject. The results of the study conclude that the media has an effect on what touches the audience so that the judge is the objective in giving a decision.